2005
DOI: 10.1111/j.1471-4159.2005.03314.x
|View full text |Cite
|
Sign up to set email alerts
|

Netrin induces down‐regulation of its receptor, Deleted in Colorectal Cancer, through the ubiquitin–proteasome pathway in the embryonic cortical neuron

Abstract: The proper regulation of temporal and spatial expression of the axon guidance cues and their receptors is critical for the normal wiring of nervous system during development. Netrins, a family of secreted guidance cues, are involved in the midline crossing of spinal commissural axons and in the guidance of cortical efferents. Axons normally lose the responsiveness to their attractants when they arrive at their targets, where the attractant is produced. However the molecular mechanism is still unknown. We inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
37
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 28 publications
(49 reference statements)
5
37
0
Order By: Relevance
“…Parenthetically, considerable attention has already been focused on the involvement of CD44 and NEUROPILIN genes in cancer cell adhesion, proliferation, invasion and metastasis (Hill et al, 2006;Nguyen et al, 2006). In coherence with our functional data, we observed that wt-DCC downregulate the expression of the SIAH1 gene (seven in absentia homolog 1) encoding the ubiquitin-conjugating enzyme Siah-1 mediating the degradation of DCC via the proteasome pathways, whereas netrin was found to exert the opposite regulation via ubiquitin-proteasome degradation of DCC (Hu et al, 1997;Kim et al, 2005). In contrast, netrin-1, but not DCC decreased the expression of a number of genes associated with cytokine/cell surface receptor-mediated signals (ADORA, CHRM1, CCL15, CYSLTR, DP1, DUSP6, EPOR, IFNGR1, IFI27, IRF8, ISGF, PRLR, TNF15, TNFR1B, TNFR21, TNFR25 and VEGF), cell adhesion and the cell matrix or motility (CLAUDIN 2, CLAU-DIN 3, FN1, INTEGRINS a3, b4, KERATIN 8-like 2, MESOTHELIN, NEUROLYSIN, PROCADHERIN 1 and TIMP3).…”
Section: Resultssupporting
confidence: 87%
“…Parenthetically, considerable attention has already been focused on the involvement of CD44 and NEUROPILIN genes in cancer cell adhesion, proliferation, invasion and metastasis (Hill et al, 2006;Nguyen et al, 2006). In coherence with our functional data, we observed that wt-DCC downregulate the expression of the SIAH1 gene (seven in absentia homolog 1) encoding the ubiquitin-conjugating enzyme Siah-1 mediating the degradation of DCC via the proteasome pathways, whereas netrin was found to exert the opposite regulation via ubiquitin-proteasome degradation of DCC (Hu et al, 1997;Kim et al, 2005). In contrast, netrin-1, but not DCC decreased the expression of a number of genes associated with cytokine/cell surface receptor-mediated signals (ADORA, CHRM1, CCL15, CYSLTR, DP1, DUSP6, EPOR, IFNGR1, IFI27, IRF8, ISGF, PRLR, TNF15, TNFR1B, TNFR21, TNFR25 and VEGF), cell adhesion and the cell matrix or motility (CLAUDIN 2, CLAU-DIN 3, FN1, INTEGRINS a3, b4, KERATIN 8-like 2, MESOTHELIN, NEUROLYSIN, PROCADHERIN 1 and TIMP3).…”
Section: Resultssupporting
confidence: 87%
“…Ligandbound netrin receptors sequester caspase-3, preventing its activation [26]. The proteasome-ubiquitin system has been implicated in DCC downregulation by netrin-1 in embryonic neurons [42]; indeed, our results are consistent with degradation controlling beta cell netrin receptor levels. The proliferative effect of netrin-1 in vascular smooth muscle cells during angiogenesis is mediated through neogenin [39].…”
Section: Unc5asupporting
confidence: 80%
“…Netrin downregulates these receptors in other cell types [42]. Indeed, exogenous netrin-1 significantly decreased neogenin and UNC5A protein levels in beta cells (Fig.…”
Section: Igf1rmentioning
confidence: 99%
“…How the activation state of cytoskeletal regulatory proteins is spatially and temporally regulated is an important question which has only been partially elucidated. Local translation, insertion and removal of receptors at the plasma membrane as well as receptor silencing all affect growth cone responses (Stein and TessierLavigne, 2001;Bouchard et al, 2004;Kim et al, 2005;Lin and Holt, 2007). Further, regulating intracellular concentrations of cyclic nucleotides affects whether neuronal processes are attracted or repelled by guidance cues in vitro and in vivo Song et al, 1998;Song and Poo, 1999;Polleux et al, 2000;Shewan et al, 2002;Nishiyama et al, 2003).…”
Section: Introductionmentioning
confidence: 99%